A disability history of the United States - Nielsen, Kim E. (Boston : Beacon Press, 2012)
Covers the entirety of U.S. disability history, from pre-1492 to the present. Disability is not just the story of someone we love or the story of whom we may become; rather it is undoubtedly the story of our nation. It places the experiences of people with disabilities at the center of the American narrative. In many ways, it's a familiar telling. In other ways, however, it is a radical repositioning of U.S. history. By doing so, the book casts new light on familiar stories, such as slavery and immigration, while breaking ground about the ties between nativism and oralism in the late nineteenth century and the role of ableism in the development of democracy. This work pulls from primary-source documents and social histories to retell American history through the eyes, words, and impressions of the people who lived it. As the author, a historian and disability scholar argues, to understand disability history isn't to narrowly focus on a series of individual triumphs but rather to examine mass movements and pivotal daily events through the lens of varied experiences. Throughout the book, he illustrates how concepts of disability have deeply shaped the American experience from deciding who was allowed to immigrate to establishing labor laws and justifying slavery and gender discrimination. Included are narratives of blinded slaves being thrown overboard and women being involuntarily sterilized, as well as triumphant accounts of disabled miners organizing strikes and disability rights activists picketing Washington. This work fundamentally reinterprets how we view our nation's past: from a stifling master narrative to a shared history that encompasses us all.
The spirit chooses the body it will occupy : indigenous North America, pre-1492 -- The poor, vicious, and infirm : Colonial communities, 1492-1700 -- The miserable wretches were then thrown into the sea : the late Colonial era, 1700-1776 -- The deviant and the dependent : creating citizens, 1776-1865 -- I am disabled, and must go at something else besides hard labor : the institutionalization of disability, 1865-1890 -- Three generations of imbeciles are enough : the Progressive Era, 1890-1927 -- We don't want tin cups : laying the groundwork, 1927-1968 -- I guess I'm an activist. I think it's just caring : rights and rights denied, 1968-
Includes bibliographical references and index.
Keywords: People with disabilities -- United States -- History; Sociology of disability -- United States -- History; People with disabilities -- Legal status, laws, etc. -- United States -- History